Performance Assessment of Road Infrastructure Affected by Traditional Market Operations in Meulaboh, West Aceh District: Evaluasi Kinerja Jalan Akibat Aktivitas Pasar Tradisional Kota Meulaboh, Kabupaten Aceh Barat - Hilma Erliana; Chaira (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
The traditional market of Meulaboh, West Aceh is a vital economic centre, but its activities put significant pressure on the surrounding road network. Research method used was to analyse the performance of a road section using the Manual of Road Capacity in Indonesia (MKJI 1997). Results of traffic flow measurements showed a consistent pattern: the highest vehicle volumes occurred on Saturday with peaks of 95.7 smp/h on Jl. Daud Dariyah (13.15-13.30) and 92 smp/h on Jl. Chik Ali Akbar (17.45-18.00). Meanwhile, Jl. Blang Pulo recorded a steady flow of over 1750 smp/hr with a DS of 0.77 (morning) and a peak of 1940.4 smp/hr (afternoon). Temporal analysis reveals a distinctive pattern where morning activity (07.00-09.00) is dominated by goods transport vehicles, while afternoons (16.00-18.00) are packed with shoppers using motorbikes. Road level of service classifications varied: from the worst condition on Jl. Daud Dariyah (level D-E) to the best on Jl. Melati (level B-C) with an average vehicle speed of 35.67 km/hour. The findings indicate an imbalance between road capacity (2299 smp/h) and traffic volumes, especially in segments adjacent to the market loading and unloading area. The comprehensive solution proposed includes management strategies for the short, medium and long term.